IBM z/OS V2R2 : diagnostics - Winnard, Keith; Hering, Paul-Robert; Salla, Alvaro (IBM redbooks., 2016)
This IBM® Redbooks® publication helps you to become familiar with the technical changes that were introduced into the Diagnostics area with IBM z/OS® V2R2. This book is one of a series of IBM Redbooks publications that take a modular approach to providing information about the updates that are included with z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic We hope you find this approach useful, and we welcome your feedback.